The Influence of Brand Image, Influencer Marketing, Online Customer Reviews, and Scarcity Marketing on Consumers' Purchase Decisions for Skintific Products on TikTok - Pungky Diana Putri; Mayla Surveyandini; Enrico Aziezy (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The rapid growth of social commerce has transformed consumer purchasing behavior, particularly in the skincare industry, where purchase decisions are shaped by multiple digital marketing factors. This study examined the effects of brand image, influencer marketing, online customer reviews, and scarcity marketing on consumers’ purchase decisions for Skintific products through TikTok. A quantitative explanatory approach was employed, involving 100 respondents who had purchased Skintific products through TikTok and were selected using purposive sampling. Data were collected through an online questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics. The findings revealed that brand image and online customer reviews had positive and statistically significant effects on purchase decisions, whereas influencer marketing and scarcity marketing had no significant effects. These results indicate that consumers place greater emphasis on brand credibility and authentic customer experiences than on influencer-based and scarcity-oriented promotional strategies when purchasing skincare products through social commerce. This study contributes empirical evidence regarding the differential effects of digital marketing factors on consumer decision-making and provides practical implications for companies seeking to strengthen their brand image and optimize customer reviews as strategic instruments for increasing purchase decisions in social commerce environments.